Lacrimacandona n. gen. (Crustacea: Ostracoda: Candonidae) from the Edwards Aquifer, Texas (USA) - Külköylüoğlu, Okan; Yavuzatmaca, Mehmet; Akdemi̇r, Derya; Schwartz, Benjamin F.; Hutchins, Benjamin T. (Zootaxa, 2017)
Lacrimacandona n. gen. with its type species Lacrimacandona wisei n. sp. from the San Marcos artesian well on the Texas State University campus (Hays County, Texas, USA) is proposed as a new genus of the subfamily Candoninae. The new species is sexually dimorphic, and so far no congeneric species have been found. The new genus has the following distinguishing characters: subtriangular carapace tapering posteriorly, uropod with a claw-like anterior seta and two short claws, one long “a” setae on male maxilliped, very large asymmetric clasping organs in males, unique shape and size of hemipenis, and unique occurrence of setae on segments.